The parent–child relationship in the digital era: The mediator role of digital parental awareness - ÖZDEN, BÜLENT (My University, 2024)
The parent–child relationship was extensively reshaped during the infusion of digital technologies into families’ daily lives. In this context, this research aims to investigate the relationship between the parent\"s time spent with the child and the parent–child relationship when digital parenting awareness including negative and positive roles is taken into consideration. A cross-sectional survey research method was employed. The data was collected by demographic information form, Child-parent Relationship, and Digital Parental Awareness scales. The data was analyzed from 285 parents with 3–6 years old children. In order to test the hypotheses, the Hayes-Process model was employed to determine the mediating effects of sub-dimensions of digital parental awareness between parent\"s time spent with the child and the parent–child relationship. The results revealed that being a negative digital role model, digital negligence, parents\" effective use of technology, and protection from digital risks partially mediate the link between parent–child time and their relationship. An increase in negative role modeling and digital negligence are associated with a decrease in the positive parent–child relationship. Furthermore, parents’ efficient use of and protection from risks from technology affects the parent–child relationship positively.
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Gelişim Psikolojisi; Sosyoloji; Genel Sosyoloji ve Metedoloji; Eğitim; Social Sciences and Humanities; Psychology; Developmental Psychology; Sociology; General Sociology and Methodology; Education; Temel Bilimler (SCI); Sosyal Bilimler (SOC); Sosyal Bilimler Genel; PSİKOLOJİ, GELİŞTİRME; SOSYOLOJİ; EĞİTİM VE EĞİTİM ARAŞTIRMASI; Natural Sciences (SCI); Social Sciences (SOC); PSYCHOLOGY; SOCIAL SCIENCES, GENERAL; PSYCHOLOGY, DEVELOPMENTAL; SOCIOLOGY; EDUCATION & EDUCATIONAL RESEARCH; Sosyal Bilimler ve Beşeri Bilimler; Gelişim ve Eğitim Psikolojisi; Sosyoloji ve Siyaset Bilimi; Social Sciences & Humanities; Developmental and Educational Psychology; Sociology and Political Science; Digital childhood; Digital parental awareness; Digital parenting; Parent–child relationship; Parent–child time